Q. 124.5( 11 Votes )

# If the function f:R → R be given by f(x) = x^{2} + 2 and g :R → R be given by find fog and gof and hence find fog (2) and gof (– 3). [CBSE 2014]

Answer :

f(x) = x^{2} + 2 and

let us find fog

⇒ fog = f(g(x))

Replace x by in f(x)

For fog(2) put x = 2

⇒ fog(2) = 6

Now let us find gof

⇒ gof = g(f(x))

⇒ gof = g(x^{2} + 2)

Replace x by x^{2} + 2 in g(x)

For gof(-3) put x = -3

**Hence fog(2) = 6 and**

Rate this question :

Fill in the blanks in each of the

Let f :R → R be defined by. Then (f o f o f) (x) = _______

Mathematics - ExemplarLet f : [2, ∞) → R be the function defined by f (x) = x^{2}–4x+5, then the range of f is

Let f : N → R be the function defined byand g : Q → R be another function defined by g (x) = x + 2. Then (g o f)3/2 is

Mathematics - ExemplarFill in the blanks in each of the

Let f = {(1, 2), (3, 5), (4, 1) and g = {(2, 3), (5, 1), (1, 3)}. Then g o f = ______and f o g = ______.

Mathematics - ExemplarLet f :R → R be defined by

Then f (– 1) + f (2) + f (4) is

Mathematics - ExemplarLet f : [0, 1] → [0, 1] be defined by

Then (f o f) x is

Mathematics - Exemplar